Fine-tuning of the Escherichia coli σ(E) envelope stress response relies on multiple mechanisms to inhibit signal-independent proteolysis of the transmembrane anti-sigma factor, RseA - Grigorova, Irina L. (Cold Spring Harbor Laboratory Press, 2004)
Proteolytic cascades are widely implicated in signaling between cellular compartments. In Escherichia coli, accumulation of unassembled outer membrane porins (OMPs) in the envelope leads to expression of σ(E)-dependent genes in the cytoplasmic cellular compartment. A proteolytic cascade conveys the OMP signal by regulated proteolysis of RseA, a membrane-spanning anti-sigma factor whose cytoplasmic domain inhibits σ(E)-dependent transcription. Upon activation by OMP C termini, the membrane localized DegS protease cleaves RseA in its periplasmic domain, the membrane-embedded protease RseP (YaeL) cleaves RseA near the inner membrane, and the released cytoplasmic RseA fragment is further degraded. Initiation of RseA degradation by activated DegS makes the system sensitive to a wide range of OMP concentrations and unresponsive to variations in the levels of DegS and RseP proteases. These features rely on the inability of RseP to cleave intact RseA. In the present report, we demonstrate that RseB, which binds to the periplasmic face of RseA, and DegS each independently inhibits RseP cleavage of intact RseA. Thus, the function of RseB, widely conserved among bacteria using the σ(E) pathway, and the second role of DegS (in addition to RseA proteolysis initiation) is to improve the performance characteristics of this signal transduction system.